Pengaruh NPM, ROA dan EPS Terhadap Harga Saham Pada Perusahaan Sub Sektor Perbankan di BEI - Ni Komang Triyanti; Gede Putu Agus Jana Susila (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine and analyze the effect of NPM, ROA, and EPS variables on stock prices in sub-sector banking companies listed on the Indonesia Stock Exchange simultaneously or partially. The research design used in this study is a causal quantitative research design. The research subjects are banking sub-sector companies listed on the Indonesia Stock Exchange and the objects in this study are NPM, ROA, EPS, and stock prices. Data were collected using the document recording method and analyzed using the multiple linear regression analysis methods. The results showed that (1) The effect of NPM, ROA, and EPS on stock prices was 85.5% (2) NPM had a positive effect on stock prices by 25.8% (3) ROA had a positive effect on stock prices by 26.4% ( 4) EPS has a positive effect on stock prices by 21.9%, which means that the ups and downs of stock prices are influenced by NPM, ROA, and EPS variables.